Geomorfološke značilnosti Tržaškega zaliva in obrobja - Orožen Adamič, Milan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2002)
The Bay of Trieste is a shallow marginal sea, the northernmost part of the Adriatic Sea surrounded by land on three sides. As it contains relatively little water, less than some large lakes, it is extremely sensitive to ecological changes. The geomorphological facts warn us that the possibilities for its exploitation are very limited. In future, a very careful, thoughtful, and balanced approach to dealing with its natural resources will be essential.Given the current lack of any long-term developmental vision, it appears that we are not sufficiently conscious of this fact.
Keywords: Adriatic Sea; geomorfologija; geomorphology; Gulf of Trieste; Jadransko morje; morsko dno; podvodni relief; Slovenia; Slovenija; Tržaški zaliv